FACTORS ASSOCIATED WITH INCREASING THE BODY'S IMMUNITY IN THE EFFORT TO PREVENT THE TRANSMISSION OF COVID-19: Literature Review - Putri Suryani Arifah; Sabillah Al Adawiyah; Apriningsih, Apriningsih (Sekolah Tinggi Ilmu Kesehatan Putra Abadi Langkat, 2021)
Coronavirus disease (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus. The impact of the spread of the spread of Covid-19 affects almost all people's lives and activities, both in terms of economy, social, education, and of course health. One of the keys to success in overcoming the transmission of Covid-19 from oneself is to increase the body's immune system or immune system so that it can strengthen the body to fight bacteria, viruses and disease-causing organisms. This study is a literature review study with the aim of knowing what factors can increase the body's immunity in an effort to prevent the transmission of Covid-19. The search was conducted using the Google Scholar database, with a systematic review. Initial search of 5,180 journal articles. After conducting a study based on the inclusion and exclusion criteria, there are 6 journal articles that can be analyzed systematically. The results of a systematic review found various factors to increase body immunity in efforts to prevent Covid-19 such as exercising/physical activity, sunbathing, eating nutritious food and drinking vitamins.